Praxis core and PLT prep. (Kaplan test prep., 2021)
"Praxis Core Academic Skills for Educators tests are frequently used as a basis for admission into teaching programs, while Praxis Subject Assessments and Praxis Content Knowledge for Teaching Assessments are often required as part of the teacher certification process. Whether you're applying for admission to a teaching program or aiming for additional certifications, Kaplan's book and online resources can help you face the Praxis with confidence."--Amazon.com.